HYDRAULICS OF GROUNDWATER FLOW AND MECHANICAL PROPERTIES AFFECTING AQUIFER SYSTEM COMPRESSION IN SHIROISHI, SAGA PLAIN - N. Cao Don; H. Araki; H. Yamanishi; K. Koga (Lowland Technology International, 2003)
Land subsidence in Shiroishi area in the Saga plain, Japan, has become noticeable since 1960s. Water supplied to agriculture has traditionally been a high priority for water managers in this region. Intense withdrawals of groundwater in excess of natural recharge have resulted in land subsidence in this region. Land subsidence can have several negative economic and social implications. Many problems associated with land subsidence can be observed in this area. In this paper, a numerical model that incorporated 3-D groundwater flow and I-D ground consolidation was applied to simulate groundwater level and ground consolidation. It is found that subsidence rapidly occurs throughout the area with the central prone in Shiroishi basin. Certain hydrogeologic parameters such as inelastic storage coefficient, elastic storage coefficient, and hydraulic conductivity of soil layers contribute significantly effects to both the rate and magnitude of consolidation. Moreover, a considerable reduction in discharge is supposed necessary for future development of the region to alleviate the effects of groundwater overdraft.